К экологии малоизвестных полужесткокрылых (Heteroptera) Европейской части СССР. Сообщение IV. Слепняки - Пучков, В.Г. (Вестник зоологии, 1971)
The article deals with a brief characteristic of locations, cycle of development апсГ
food relations in more than 20 Heteroptera species. Some of these species are new for
fauna of the Soviet Union.